Pengaruh Online Customer Review dan E-Service Quality terhadap Keputusan Pembelian Konsumen pada Platform ShopeeFood dengan Minat Beli sebagai Variabel Intervening - Muhammad Sa'idun; Ibnu Khajar (Lembaga Yasin AlSys, 2025)
The growth of digital food delivery services has driven changes in consumer behavior, including increasingly intensive use of the ShopeeFood platform. This study aims to analyze the influence of online customer reviews and e-service quality on purchase decisions, with purchase intention as an intervening variable, among ShopeeFood users in Semarang City. A descriptive-verificative quantitative approach was employed using a survey method with questionnaires administered to 151 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that online customer reviews and e-service quality have a positive and significant effect on purchase intention, and they also have a positive effect on purchase decisions both directly and indirectly through purchase intention as a mediating variable. These findings confirm that high-quality consumer reviews and good digital service quality can enhance consumer trust, interest, and purchase decisions. The study concludes that more systematic management of customer reviews and optimization of electronic service quality can serve as effective strategies to increase purchase decisions in food delivery services, with practical implications for ShopeeFood in designing marketing strategies, developing application features, and strengthening overall digital service quality.